Risk estimation in familial adenomatous polyposis using DNA probes linked to the familial adenomatous polyposis gene. - Koorey, D J (1992)
The familial adenomatous polyposis gene has recently been assigned to the long arm of chromosome five through linkage to several 5q DNA probes. These probes can now be used to trace inheritance of the disease gene in affected families. In this study, DNA samples from 152 members of 10 Australian familial adenomatous polyposis families have been examined for restriction fragment length polymorphisms detected by DNA probes C11P11, ECB27, and YN5.48. Linkage analysis confirmed linkage between the familial adenomatous polyposis gene and each probe with a maximum combined LOD score of 2.82 for C11P11, 2.90 for ECB27 and 5.49 for YN5.48 all at a recombination fraction of zero. Risk estimates were determined for the 51 at risk individuals in these families based on their restriction fragment length polymorphism data alone or in addition by including the effect of age dependent penetrance. Thirty two of those at risk (63%) could be assigned specific high (greater than or equal to 95%) or low (less than or equal to 5%) risks of developing familial adenomatous polyposis on the basis of their probe results. When the effect of age dependent penetrance was included, 26 (51%) fell at the extremes of risk (greater than or equal to 99% or less than or equal to 1%). Such estimates provide a sound basis for planning sigmoidoscopic screening of at risk family members and will thus facilitate surveillance in familial adenomatous polyposis families.